THE PROBLEM OF JUSTIFICATION OF THE STATE SECTION IN THE ROAD CONSTRUCTION PROJECT ON THE CONCESSION BASIS (International Journal of Innovative Technologies in Economy, 2021)
In the proposed article, an attempt is made to resolve one of the most pressing issues that arise when justifying the implementation of road construction projects on a concession basis. This is a question of state participation in co-financing the project. The task has a double limitation. On the one hand, the opportunities for state participation in such projects are limited by the financial resources of the State Road Fund. On the other hand, the state's participation is limited by the project's internal capacity to provide sufficient cash flow.The criteria for selection of projects implemented in the transport sector were studied. Additional requirements for the adequacy of expected cash flows have been formulated for projects that are expected to be implemented on a concession basis. The first step involves determining the creditworthiness of the project. The second is to ensure the required rate of return for private investors. The third step determines the need for state participation in co-financing the project and its respective share.